The Influence of Synthesis Temperature on the Structure, Composition and Magnetic Properties of Nanocomposites NiCo/C - D.G. Muratov; L.V. Kozhitov; S.G. Emelyanov; E.V. Yakushko; M.F. Bulatov (Журнал нано- та електронної фізики)
By method of IR-pyrolysis the precursor of polyacrylonitrile and compounds of cobalt and nickel metalcarbon nanocomposites were obtained, representing nanoparticles of alloy NiCo, dispersed in nanocrystalline carbon matrix. NiCo / C nanocomposites are ferromagnets. Magnetization and the coercive force depends on the size and composition of the alloy nanoparticles NiCo. The average size of metal nanoparticles is determined by the synthesis temperature and in range of 350-800 °C is 10-80 nm, respectively. According to the results of TEM it was detected that with increasing synthesis temperature the maximum synthesis of nanoparticles size distribution shifts to larger sizes. The magnetization and coercivity depend on the size and composition of the nanoparticles of alloy NiCo. With increasing synthesis temperature from 350 to 800 °C the magnetization increases from 0.055 to 17 A·m2/kg.